PENGARUH KREDIBILITAS INFLUENCER DAN BRAND AWARENESS TERHADAP MINAT PEMBELIAN DI TOKOPEDIA (Studi Pada Pelanggan Tokopedia yang Bertransaksi Melalui Bank Syariah Indonesia) - Yulia Tiara Putri; Rita Kusumadewi; Eef Saefulloh (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
Tokopedia is the largest e-commerce company in Indonesia. Company can increasing their customers interest through credibility influencer and brand awareness. Influencers are one of the factors that contribute the company's progress and to increase brand awareness, which is later intended to emerge in a purchasing decision The results showed that the first hypothesis was accepted, that the Influencer credibility variable had a positive and not significant effect on Tokopedia purchase Interest. with a partial effect of 43.1%. The second hypothesis is accepted, that the Brand Awareness variable has a positive and significant effect on Tokopedia Consumer Interest, with a partial effect of 54.7%. The third hypothesis is accepted, that the influencer and brand awareness variables simultaneously have a positive and significant effect on Tokopedia purchase interest with a simultaneous influence of 59.1%.